The implementation of Cognitive Strategy Instruction in Writing (CSIW) strategy in teaching writing for the eight grade students at Mts Al-Karomah Winong Ngawi - Ita Karlinasari (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
Teaching and learning English in junior high school has the goal of focusing the students' ability to use English in every skill. One of the skills in this level is writing. Writing as one of four skills in language is a difficult one, especially for Junior High school. The purposes of the research are to describe the implementation of CSIW strategy, the advantages and the disadvantages in using CSIW strategy, and the students' response to implementation of CSIW strategy in teaching writing. The researcher offers CSIW strategy to solve those problems by improving the students' writing skills. The implementation of CSIW strategy in teaching writing for the eighth grade students at Mts Al-Karomah in the school year of 2015/2016 has three steps, they are pre-activity, whilst-activity, and post-activity. The results of implementing these three activities in class are the students become more directive in writing recount text, they show, the reason, how to write in their story well and the topic clearly. The students are also more active and concentrate on the learning process. Based on the result, it suggested that the teacher should use a strategy when they learn English especially in teaching writing. The students should make the draft/organization of written text before exploring it into their writing. It can help them to do exercise.